Impact of CO2 permeation on inter–layers and reservoir caprock sealing efficiency - Al Sayah, Ali Farag A (2025)
Carbon capture and storage (CCS) is expected to play a vital role in achieving greenhouse gas reduction targets. The key stage of the CCS system is storing the carbon dioxide (CO2) into geological formations safely for millions of years. This cannot be achieved without comprehensive investigation of the caprock/seal integrity. The need to find sufficient capacity for geological CO2 storage to meet demand means less than ideal, heterogeneous reservoirs need to be considered. Many such reservoirs are apparently compartmentalised by thin inter–layers, and have complex caprock structures, including, faults, fractures, chimney–like structures, heterogeneity in thicknesses, and petrophysical properties. The literature surveyed indicated that the subsequent evolution of the caprock and reservoir following exposure to scCO2 involves a complex coupling of geomechanics, geochemistry, and mass transport processes over different lengths and time scales. The combination of all three factors together is rarely considered but is required to properly test the feasibility of the storage site. Further, significant research gaps were identified regarding the effects of complicated, intricate processes affecting shale inter–layer (or seal) integrity under realistic reservoir conditions. This thesis investigates the impact of shale inter–layers of thicknesses below seismic resolution that are generally neglected in plume migration simulations, but have been shown here to be important. Only simulations of plume migration that include coupling of all three of mass transport, geo–chemical and geo–mechanical processes together provide proper prediction of the barrier efficiency of relatively thin shale inter–layers in ‘Sleipner–like field’. Furthermore, the research investigated the importance of intricate feedback interactions, occurring in systems with complex seal and reservoir geologies, for controlling the overall plume migration behaviour in a model of a ‘Bunter–like’ storage site. This was done by comprehensive numerical simulation of various scenarios using 3D static models based on geological structures found in the Sleipner and Bunter fields and then preforming fully coupled flow–mechanical–chemical simulations using compositional simulator CMG–GEM software. The simulation results showed a series of feedback inter–actions between these three process types. These have been studied in detail, and, for example, lead to the unexpectedly higher barrier efficiency of thin inter–layers compared to slightly thicker inter–layers. The results show that capillary breakthrough pressure, diffusion processes and the re–activation of natural fractures played a vital role in enhancing the migration of the CO2 plume via the thicker shale inter–layers towards the overburden. In addition, the findings indicated that the use of an oversimplified caprock model, which assumed only a single impermeable caprock layer and no CO2 leakage, would give rise to misleading conclusions about CO2 plume migration. When comparing CO2 plume migration between scenarios with either a multi–layered, variegated caprock, or just a single caprock, it was found that 20% of the injected CO2 leaked in the former, whereas no leakage was observed through the latter. The presence of a chimney–like structure, within a multi–layered caprock, facilitated lateral CO2 plume movement due to advection forces, unlike with a single, uniform caprock. Also, in a scenario with both shale inter–layers in the reservoir, and a chimney in the caprock, while, during the post–injection period, fracture re–activation was observed in the upper inter–layer near the chimney zone in both multi–layer and single caprocks, this occurred significantly earlier for the former compared to the latter. The presence of a chimney in the caprock led to significant localised downward CO2–rich brine fingering in the reservoir below, caused by gravitational instability and heterogeneity in petrophysical properties, due to leakage through the chimney. Larger fault re–activation was noted in multi–layered caprocks, when compared to a single caprock. Calcite mineral changes significantly influenced caprock porosity across all Cases considered, while halite changes within sub–layers varied between multi–layer and single caprocks. Over the 1000–year simulation period, most of the injected CO2 remained in the supercritical phase, followed by dissolution trapping of the CO2, hysteresis trapping, and finally, mineralisation. The long–term spreading behaviour of the leaked fraction of the plume is very different for multi–layer, as opposed to a single layer, caprocks.